Lao People's Democratic Republic : 2005 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Lao People's Democratic Republic. (IMF Staff Country Reports; Country Report, 2006)
The macroeconomic performance for Lao People's Democratic Republic is encouraging, but underlying fragilities remain. Progress needs to be made on structural reforms. On the fiscal side, the immediate challenge is to avoid an unsustainable expansion of spending. The medium-term priority is to mobilize revenues to enable Lao People's Democratic Republic to meet its development needs, within a sustainable fiscal framework. Progress under the Public Expenditure Management Strengthening Program is essential to strengthen fiscal management. The country's high debt burden requires prudent debt management.